Riojan Martyrs: Seeds of the Gospel in the Inland (Res Gesta, 2020)
Pope Francis, in April 2019, proclaimed the beatification of Enrique Angelelli -Bishop of La Rioja-, Carlos de Dios Murias and Gabriel Longueville -priests-, and Wenceslao Pedernera, father of a family and catechist, all four of them murdered by the hand of State terrorism in 1976. Within this framework, a joint activity was held at the Universidad Católica Argentina, in Rosario on June 24, 2019, with the Archbishopric of Rosario, the Social Pastoral, the Institute for the Integration of Knowledge and the Faculty of Law and Social Sciences of Rosario. The objective of this activity was to rescue the memory of these martyrs through the testimony of witnesses of their lives.The meeting included the first-person testimony of Fr. Luis Cossia, a Capuchin Franciscan who worked in the Olta Parish during the period when Angelelli occupied the Episcopal See of La Rioja; Pbro. Miguel Ángel La Civita, the current parish priest of Villa Eloísa, who was a seminarian in La Rioja in the 1970s; Mari Révora, a teacher and mother committed to the Rural Movement of Catholic Action, who knew Wenceslao Pedernera personally; and Monsignor Roberto Queirolo, who had a profound knowledge of the pastoral style of the Rioja diocese in Angelelli's time.The following is a literal transcription of the memories and testimonies that they shared before a large audience.